Study on structural transformation of molybdenum oxide catalyst for propane oxydehydrogenation (ODH) reaction / Durga Devi Suppiah - Suppia, Durga Devi (2012)
Catalytic oxidative dehydrogenation (ODH) of propane is recognized as an attractive alternative process as compared to propane dehydrogenation which the latter requires higher reaction temperature. For ODH of propane, key points in synthesizing an active catalyst are the preparation method, surface reducibility, and acid-base properties. However, existing ODH catalysts gives low activity and poor selectivity. Combination of optimal activation thermal analysis and structural control can help to guide and gain insight into the structure-activity relationship of the nanostructured catalyst system. Molybdenum and vanadium oxide based catalyst has been identified as one of the most suitable catalyst for the reaction. However it is difficult to control the key properties such as crystal size, structure, particle shape and surface area that influence the catalysts performances. In these studies, molybdenum oxides based catalysts (MoOx and MoVOx) were synthesized using controlled precipitation method. Parameters varied were pH, concentration, temperature and also rate of addition. For MoOx based catalysts, the phase obtained were ‗supramolecular‘ phase (Mo36O112) and hexagonal phase (h-MoO3). Protonation encourages the growth of the catalytic structure where Mo7O24 acts as a nucleus creating the polyoxomolybdates. Both phases have bulk structural corner sharing pentagonal channels as structural motif which is catalytically active. For MoVOx based catalyst, amorphous phase was observed for all spray dried precursors. Highly crystalline hexagonal phase (MoV2O8) and tetragonal phase [(MoV)5O14] were obtained after activation under static air and inert respectively when vanadyl was used as the vanadium source. Dispersion of vanadium creates the ‗site isolation‘ effect which is important to avoid olefins transforming to neighboring oxidized sites. When vanadates were used as the vanadium source, different phases were observed at varying of vanadium loading. Orthorhombic phase was observed at low vanadium loading whilst mixed phase of monoclinic and triclinic were obtained at higher vanadium loading. Temperature programmed activation using in-situ XRD was used to study the dynamics of structural transformation of selected synthesized molybdenum oxide-based precursor. The structural evolution for MoOx precursor takes place from ‗supramolecular‘ to metastable hexagonal phase at 300 ºC. The structural changed finally to the stable orthorhombic phase at 450 ºC. For MoVOx precursor, the structural transformation takes place from amorphous to nanocrystalline phase at 400 ºC. At 500 ºC, the catalyst morphology transforms finally to thermodynamically stable crystallized tetragonal phase. By correlating in-situ XRD reactivity studies with temperature programmed in-situ DSC, catalytic activity in MoOx catalyst was not observed whilst for reaction using MoVOx catalyst, catalytic activity was observed at the nanocrystalline phase.